ENHANCING LISTENING SKILLS OF EFL LEARNERS BY MEANS OF PODCASTS - Umaraliyeva, Munojat Mashrabovna; Bozorboyeva , Omina Aliyevna (Educational Research in Universal Sciences, 2023)
This scientific article aims to explore the potential benefits of incorporating podcasts as a tool to enhance the listening skills of English as a Foreign Language (EFL) learners. While traditional listening activities focus primarily on textual materials and face-to-face interactions, podcasts offer an innovative and engaging approach to language learning. This article presents the theoretical background supporting the use of podcasts in EFL education, discusses the advantages of incorporating podcasts in listening instruction, and presents empirical evidence on the effectiveness of podcasts in improving EFL learners’ listening skills. Three relevant studies that highlight the positive impact of podcast-based listening activities are cited and analyzed.